Exploring the Needs of Industry 4.0: Soft Skill Development Based on Vocational Education in Higher Education - Petra Adamcova, Petra Adamcova (Edu Learning, 2025)
Revolution 4.0 is an era when the technology is developing very rapidly marked by the emergence of Artificial Intelligence (AI), in this era also the qualifications of the workforce needed are increasingly diverse, especially in the soft skills possessed by the workforce. Vocational education as an institution oriented towards producing competent graduates and having high professionalism in this era is required to be able to participate in fulfilling these qualifications. This research aims to analyse the soft skills that must be possessed by each graduate and to analyse soft skill development methods that are suitable for the industrial revolution 4.0. This research uses a qualitative method with a literature study approach taken from journals, research and books. From the results of the analysis, it was found that there are three soft skills that must be possessed by each graduate, namely the ability to think critically, the ability to solve problems, the ability to communicate and collaborate, as well as further attention to aspects of emotional intelligence. In addition, a practice-based soft skill development method was also found, namely simulation-based learning (SML) which is in line with technological developments by involving various real and virtual devices.